PENGARUH KOMITMEN ORGANISASIONAL DAN GAYA KEPEMIMPINAN TERHADAP TURNOVER INTENTIONS KARYAWAN - fachrudy asjari (Majalah Ekonomi, 2016)
This research intended to asses the organizational commitment, leadership style to the turnover intentions which must be performed in PT. Aneka Jasa Grhadika. This research was conducted in Gresik which covered 72 employee and a few of manager as respondent. This research by utilizing Regression, the technique was processed with SPSS 20.0 to analyze some hypothesis. The intercorrelations models between two variables in this study revealed that the hypothesis have significant correlation. The result of this research were empirical date of the development of the theoretical of human resoureces and practice management. Key words: Komitmen Organisasional, Gaya Kepemimpinan dan Turnover Intentions.